Entrepreneurship Education in KwaZulu-Natal High Schools: Fostering Skills and Mindsets - Thandukwazi Richman Ncube; Mpubane Emanuel Matlala (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Entrepreneurship is increasingly recognized as a critical driver of economic growth, innovation, and job creation, particularly in developing countries like South Africa, where high unemployment rates and economic inequalities persist. In this context, entrepreneurship education has become a pivotal strategy in preparing the younger generation to embrace entrepreneurial mindsets and develop the skills necessary to succeed in the modern economy. South Africa’s National Development Plan emphasizes the need to develop entrepreneurial capacity at all levels of education, particularly in high schools, where early exposure to entrepreneurial concepts can ignite interest and cultivate essential skills for future business ventures. This study explores the role of entrepreneurship education in fostering entrepreneurial mindsets and skills in KwaZulu-Natal government-funded high schools, in South Africa. Using a quantitative research approach, the study revealed that a majority of educators perceive entrepreneurship education as essential for equipping students with entrepreneurial skills, enhancing economic literacy, and contributing to the reduction of unemployment. Key entrepreneurial skills such as creativity, innovation, and risk-taking were highlighted as critical outcomes of the curriculum. However, the results also showed inconsistencies in the implementation of outreach programs, limited collaboration with industry professionals, and the need for greater institutional support. The study concludes that while entrepreneurship education in KwaZulu-Natal high schools positively impacts students, several areas require improvement. Key recommendations include enhancing curriculum design to include more experiential learning, providing professional development for educators, strengthening public-private partnerships to offer practical learning opportunities, increasing governmental support for program implementation, and establishing regular assessments to ensure the effectiveness of entrepreneurship education.